The role of polo‐like kinase 3 in the response of BRAF‐mutant cells to targeted anticancer therapies. Issue 1 (30th September 2019) - Babagana, Mahamat; Kichina, Julia V.; Slabodkin, Hannah; Johnson, Sydney; Maslov, Alexei; Brown, Lorin; Attwood, Kristopher; Nikiforov, Mikhail A.; Kandel, Eugene S.
Abstract: The activation of oncogenic mitogen‐activated protein kinase cascade via mutations in BRAF is often observed in human melanomas. Targeted inhibitors of BRAF (BRAFi), alone or as a part of a combination therapy, offer a significant benefit to such patients. Unfortunately, some cases are initially nonresponsive to these drugs, while others become refractory in the course of treatment, underscoring the need to understand and mitigate the underlying resistance mechanisms. We report that interference with polo‐like kinase 3 (PLK3) reduces the tolerance of BRAF‐mutant melanoma cells to BRAFi, while increased PLK3 expression has the opposite effect. Accordingly, PLK3 expression correlates with tolerance to BRAFi in a panel of BRAF‐mutant cell lines and is elevated in a subset of recurring BRAFi‐resistant melanomas. In PLK3‐expressing cells, R406, a kinase inhibitor whose targets include PLK3, recapitulates the sensitizing effects of genetic PLK3 inhibitors. The findings support a role for PLK3 as a predictor of BRAFi efficacy and suggest suppression of PLK3 as a way to improve the efficacy of targeted therapy.